The United Nations Convention on the Rights of Persons with Disabilities and Mental Health Law - Bartlett, Peter (2012)
The United Nations Convention on the Rights of Persons with Disability (CRPD) took effect in 2008. This paper discusses a number of flashpoints where the CRPD will require real and significant reconsideration of English mental health and mental capacity law. The CRPD introduces a new paradigm into international disability law, relying on the social model of disability. While that is no doubt a good thing, there is as yet no clear sense as to how that is to be implemented. After providing an introduction to the Convention, the paper considers four specific areas: mental capacity law (focussing on the provisions of the Mental Capacity Act 2005), psychiatric treatment without consent, civil detention of people with mental disabilities, and mental disability in the criminal system (fitness to plead, insanity and diminished responsibility).